Antibacterial activity, metabolites and elemental analysis of Saussurea candicans C. B. Clarke - Puri, Shweta; Sidhu, M.C.; Sharma, Avantika (Current Botany, 2017)
Phytochemical analysis of ethanol and water extracts of Saussurea candicans has indicated the presence of flavonoides, phenolics, tannins etc. that supports its use in traditional medicine both for human and animals in different parts of the world. S. candicans is a plant of medicinal interest hence selected for analysis. Antibacterial activity of the two extracts was tested against Enterococcus faecalis, Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus. Only the ethanol extract was found to be effective. Both aqueous and ethanol extracts were prepared and studied for different phytochemicals like alkaloids, flavonoides, phenolics, steroids etc. and also for their antibacterial activity using agar well diffusion method. The Fourier Transform Infrared (FTIR) and Wavelength Dispersive X-Ray Fluorescence (WD-XRF) spectroscopy of whole plant powder were done to study the functional groups and elemental profile, respectively. The aqueous extract contains more (11) phytochemicals as compared to ethanol (9). No zone of inhibition was observed at different volumes of the extract i. e., 20Î¼l, 50Î¼l and 100Î¼l but at 150Î¼l and 200Î¼l concentration of 230.7 mg/ml plant extracts, the zone of inhibition was reported. The dose of 150Î¼l concentration active only against E. faecalis, whereas, 200Î¼l concentration showed activity against all bacterial strains. Only the ethanol extract had antibacterial activity against all the tested bacteria. The medicinal activity of S. candicans is assumed to be because of the presence of different phytochemicals and elements. Further study can be conducted to understand the role of each and every reported phytochemicals and elements.Â 